1998
DOI: 10.1111/j.1439-0450.1998.tb00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytological, Immunocytochemical and Biochemical Cerebrospinal Fluid Investigations in Selected Central Nervous System Disorders of Dogs

Abstract: Cerebrospinal fluid (CSF) obtained from 20 clinically healthy dogs and from 15 dogs affected by neurological disorders were examined for total and differential cell counts, immunocytochemistry for canine distemper virus antigen, total protein concentration and electrophoretic separation, and glucose and enzyme determination. Dogs affected by canine distemper showed an increase in macrophages, presence of specific inclusion bodies, and an increase in total protein concentration and gamma-globulin fraction. In b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 6 publications
1
26
1
1
Order By: Relevance
“…Also, this globulin had values a little higher than the normal range reported by Sorjonen (1987), Sorjonen et al (1989) and Thomas et al (1993). An increase in CSF γ-globulins was seen in dogs with distemper, which was also observed in this research for animals of G3, despite the levels of this globulin in this study were much higher than reports from many investigators (Cutler and Averill, 1969;Abate et al, 1998). The magnitude of the blood-brain barrier harm and γ-globulins transudation could be the explanation for the changes found in this study, but it deserves to emphasize the possibility of local production of immunoglobulins within the nervous system, or both concurrently.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Also, this globulin had values a little higher than the normal range reported by Sorjonen (1987), Sorjonen et al (1989) and Thomas et al (1993). An increase in CSF γ-globulins was seen in dogs with distemper, which was also observed in this research for animals of G3, despite the levels of this globulin in this study were much higher than reports from many investigators (Cutler and Averill, 1969;Abate et al, 1998). The magnitude of the blood-brain barrier harm and γ-globulins transudation could be the explanation for the changes found in this study, but it deserves to emphasize the possibility of local production of immunoglobulins within the nervous system, or both concurrently.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, the results from both groups were within the reference range (Krakowka et al, 1987;Sorjonem, 1987). The albumin fraction reported for these groups corresponds to nearly 30% of CSF total protein, which was also observed by Sorjonem (1987) and Abate et al (1998). However, it did not confirm a preceding investigation of Mayhew and Beal (1980), which showed that normal cerebrospinal fluid protein is composed almost entirely of albumin.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Others speculate that high creatine kinase activity results from blood contamination of the fluid sample due to changes in permeability of the blood-brain barrier (Indrieri et al 1980;Wilson 1977). Abate et al (1998) postulated that during neurological diseases, these enzymes are released in CSF as a consequence of tissue damage and/or increased permeability of the blood brain barrier. Heavner et al (1986) found approximately 10 times higher activity of the LDH in serum, than in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Cul ebr as-Fer nández (1971) stated that diseases chronically affecting gray matter and acute, extensive diseases of CNS may cause elevation in the LDH levels, whereas diseases affecting the myelin may cause elevated values of CK in people. In veterinary medicine the CSF CK activity was evaluated in dogs (Abate et al 1998;Indrieri et al 1980;Wilson 1977;Wright 1980) and horses (Furr and Tyler 1990;Jackson et al 1996). Creatine kinase activity was increased in cases of feline toxoplasmosis and feline infectious peritonitis (Wilson 1977).…”
mentioning
confidence: 99%